MONITORING AND PROSECUTING THE ILLEGAL ELEPHANT IVORY TRADE IN INDONESIA - dewi, Adelia aprianti (Communale Journal, 2024)
Indonesia is also estimated to have as many as 300,000 species of wildlife, and as many as 17% of animals worldwide are found in Indonesia.  One of the problems is the declining elephant population and the lack of public knowledge about protected animals, such as the illegal ivory trade and the decline in the elephant population due to poaching for ivory. Illegal wildlife trade poses a serious threat to wildlife conservation in Indonesia.  Until now, there are still cases of the illicit trade in elephant ivory that cause endangerment caused by several factors; illegal wildlife trade has obstacles and obstacles in its enforcement, including the lack of knowledge and supervision of law enforcement officials on protected wildlife management, so that the identification of animal species becomes difficult and takes a long time because of the many smuggling routes both on land and at sea. Also, the threat of sanctions does not provide a deterrent effect for the perpetrators. This also encourages people to continue committing illegal protected wildlife trade acts. This research aims to understand and analyze the effectiveness of law enforcement and the obstacles faced in law enforcement, the method used in this research is the normative legal research method which focuses on the study of legal norms that exist in legislation, legal doctrine, and legal theories, with the approach of relevant legislation and legal issues to find legal solutions and find the truth and case approaches.